Application of Economic Production Quantity (EPQ) Method and Just in Time Method (JIT) in Bread Raw Material Inventory Control - Kisty, Teshi Amelia Hakilla; Safitri, Elfira; Basriati, Sri; Soleh, Mohammad (Zeta - Math Journal, 2025)
Retno bakery Bread Shop is one of the shops that produces various types of bread. This bakery has not used a inventory control system in the production process so it cannot meet customer needs. For this reason, Retno Bkery Bakery needs to control inventory so that the company's performance and profits are more optimal. This study discusses the control of the inventory of each bread raw material such as flour, sugar, milk, yeast, salt, butter and eggs. The purpose of this study is to obtain the results of the total cost of bread raw material inventory using the Economic Production Quantity (EPQ) method and the Just in Time (JIT) method as well as the comparison of the two methods used. The methods used are the Economic Production Quantity (EPQ) and Just in Time (JIT) methods. Based on the results of the study, the percentage difference in cost for each raw material was obtained using the Economic Production Quantity (EPQ) method and the Just in Time (JIT) method, namely for flour raw materials of 42.05%, sugar 47.31%, milk 51.63%, yeast 51.83%, salt 47.65%, butter 51.38% and eggs 51%. Thus, the Just in Time (JIT) method results in a smaller total cost than the Economic Production Quantity (EPQ) method.